Exploring facial overfilled syndrome from the perspective of anatomy and the mismatched delivery of fillers - Lim, Ting‐Song; Wanitphakdeedecha, Rungsima; Yi, Kyu‐Ho (Journal of cosmetic dermatology, 2024)
Introduction Facial fillers and injectables have transformed the landscape of cosmetic procedures, offering rejuvenation possibilities. However, the emergence of “Facial Overfilled Syndrome (FOS)” presents a concerning trend attributed to excessive filler use and suboptimal injection techniques. Understanding the interplay between facial aging and augmentation techniques is crucial in addressing and preventing FOS. Material and Methods Facial overfilled syndrome is characterized by the excessive use of fillers, resulting in a distorted and heavy appearance. It manifests in various forms, including 'flowerhorn' foreheads, 'sunset' eyes, 'chipmunk' cheeks, 'witch' chins, and 'pillow' faces. The syndrome arises from attempts to combat anatomical aging with dramatic filler treatments, causing rapid volume changes and skin tightening. Skeletal structures and soft tissue distribution across different ethnicities play a significant role in FOS development. Results Understanding the aging process across facial tissues is essential, as fillers cannot entirely reverse aging manifestations. Tailored assessment and treatment plans should precede filler injections, involving muscle assessment, observation of facial movements during injection, and ultrasound imaging of fat layers. Attention should be given to filler pressure and migration risks, particularly in areas with elevated pressure. Additionally, alternative approaches like energy‐based devices and polymer reinforcement of facial ligaments should be considered to minimize filler use. Ethnic variations in facial anatomy require careful consideration to avoid overcorrection. Conclusion FOS predominantly affects individuals of East Asian descent due to specific facial characteristics. Prevention strategies involve minimizing filler use, addressing underlying bone changes, and considering ethnic and gender differences in facial anatomy. Recent MRI and ultrasound studies challenge the notion of filler breakdown, emphasizing the importance of filler selection and injection techniques. Education, individualized treatments, and a holistic understanding of facial anatomy are key to preventing and managing FOS and ensuring natural and harmonious facial aesthetics.